Factors Affecting Management Profit in Non-Financial Companies Listed on BEI - Hafizafahri Ranggala; Rudiansyah Yuliatma (Budapest International Research and Critics University, 2022)
The purpose of this study is to obtain empirical evidence about the effects of managerial ownership, institutional ownership, board size, income tax, leverage, profitability, audit quality and auditor independence on earnings management in non-financial companies in Indonesia. This study uses non-financial companies listed on the Indonesia Stock Exchange (BEI) for three years, from 2016 to 2018. Using a purposive sampling method that sets five sample criteria, obtained 165 companies. This study uses multiple regression in data analysis. The results showed that the income tax, leverage and profitability variables had an influence on earnings management, while other variables namely managerial ownership, institutional ownership, board size, audit quality and auditor independence had no influence on earnings management practices in a company.